Hubungan Antara Paritas Ibu Dengan Kejadian Plasenta Previa Di Ruang Kebidanan Rsud Dr. H Abdul Moeloek Provinsi Lampung - Ana Mariza; Desi Risna Purnamasari (Universitas Malahayati Lampung, 2021)
ABSTRACT :RELATIONSHIP BETWEEN MOTHER'S PARITY AND EVENTS IN THE PLASENTA PREVIA MIDWIFERY HOSPITAL DR. H ABDUL MOELOEK LAMPUNG PROVINCE Introduction: According to WHO in 2010 as many as 356,000 women died due to childbirth problems, maternal mortality was caused by several factors, including bleeding, one of the causes was placenta previa. The frequency of placenta previa increases in high parity, old age, uterine defects such as cesarean section, curettage, myomectomy and so on. Purpose :this study was to determine the relationship between maternal parity and the incidence of placenta previa in the obstetrics room of Dr. H Abdul Moeloek, Lampung Province.Method : This research was conducted using an analytic design with a cross sectional approach. The population in this study were all mothers giving birth at RSUD Dr. H Abdul Moeloek in 2015, which numbered 1435 people. Samples taken using systematic random sampling of 313 people. The analysis used was univariate analysis, namely by presentation and bivariate by chi squere.Result : The results obtained from the study of the frequency of mothers who experienced placenta previa were 49 (15.7%) people, the distribution of the frequency of parity at risk in labor was 193 (61.7%) people, There was a relationship between maternal parity and the incidence of placenta previa based on statistical tests obtained P value = 0.008 with the result of the OR value = 2.786.Conclusion : Suggestions from researchers are that the hospital is expected to further improve human resources by holding training or seminars for midwifery room employees, installing placenta previa protocols in the obstetrics room so that they can improve supervision of both the delivery process with placenta previa or the factors that cause placenta previa. Keyword : Parity, Plasenta Previa INTISARI : HUBUNGAN ANTARA PARITAS IBU DENGAN KEJADIAN PLASENTA PREVIA DI RUANG KEBIDANAN RSUD DR. H ABDUL MOELOEK PROVINSI LAMPUNG Latar Belakang :Menurut WHO pada tahun 2010 sebanyak 356.000 perempuan meninggal akibat masalah persalinan, kematian ibu disebabkan beberapa faktor diantaranya adalah faktor perdarahan, salah satu penyebabnya adalah plasenta previa. Frekuensi plasenta previa meningkat pada paritas tinggi, usia lanjut, cacat rahim misalnya bekas bedah sesar, kuretase,miomektomi dan sebagainya.Tujuan: tujuan penelitian ini adalah mengetahui hubungan antara paritas ibu dengan kejadian plasenta previa di ruang kebidanan RSUD Dr. H Abdul Moeloek Provinsi Lampung.Metode penelitian :Penelitian ini dilakukan dengan menggunakan desain analitik dengan pendekatan cross sectional. Populasi pada penelitian ini adalah seluruh ibu bersalin di RSUD Dr. H Abdul Moeloek pada tahun 2015, yang berjumlah 1435 orang. Sample yang di ambil menggunakan systematic random sampling sejumlah 313 orang. Analisa yang digunakan adalah analisa univariat yaitu secara presentasi dan bivariat secara chi squere.Hasil : Didapatkan hasil penelitian frekuensi ibu yang mengalami plasenta previa sebanyak 49 (15.7 %) orang, Distribusi frekuensi paritas beresiko pada ibu bersalin sebanyak 193 (61.7 %) orang, Terdapat hubungan antara paritas ibu dengan kejadian plasenta previa berdasarkan uji statistik didapat P Value = 0,008dengan hasil nilai OR =2.786. Kesimpulan : diharapkan rumah sakit lebih meningkatkan SDM dengan diadakannya pelatihan ataupun seminar bagi pegawai ruang kebidanan, memasang protab-protab plasenta previa di ruang kebidanan sehingga dapat meningkatkan pengawasan baik proses persalinan dengan plasenta previa atau faktor-faktor penyebab terjadinya plasenta previa. Kata Kunci : Paritas, Plasenta Previa